Will they hear me now? : medical advocacy and how to be effective - Keppel-Colkitt, Kathy (BMC Enterprise, 2025)
"When Kathy's daughter, Brandi was diagnosed with cancer and given a 95% cure rate, yet died four months later, there arose a lot of questions regarding the quality of her medical care both up to and after her diagnosis. She found the doctor-patient relationship lacking as she was met with many errors and incompetence. The need for a Medical Advocate in situations such as these became clear. Kathy's visceral book shares her daughter Brandi's tragic journey, which brings to light how and why having an Advocate and Liaison is vital in crisis situations of all types. Kathy explains the roles of a Medical Advocate and Liaison, and provide tools and resources for effective Advocacy."--